Evaluating environmental mediation: Mediation in the waste management programme of Neuss County, Germany. Results of a participant survey - Katharina Holzinger (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Little empirically based social scientific research has been carried out with the aim of evaluating mediation procedures. Generally, such procedures are evaluated retrospectively and on the basis of very general criteria (Was an agreement achieved?). The Social Science Research Centre Berlin (WZB) is conducting a research project into mediation procedures in the field of environmental protection, the central object of study being the mediation procedure undertaken to resolve the dispute over the waste management programme of Neuss County in Germany. This paper presents some results of the accompanying social scientific research, with the aim of evaluating the success of the mediation. It begins by describing the problems underlying the mediation procedure in Neuss, the procedure itself and the results achieved. There then follows an evaluation of this procedure, based on 18 key procedural and results-related criteria for evaluating the success of the mediation. The analysis shows that the evaluation of mediation procedures is a highly complex affair, and that this is reflected in the evaluations made by the participants themselves. – – Zur Evaluation von Mediationsverfahren in der Umweltpolitik gibt es bisher kaum empirisch fundierte sozialwissenschaftliche Forschungsergebnisse. In vielen Fällen werden Mediationsverfahren aus der Rückschau und auf der Basis sehr allgemeiner Fragestellungen (Wurde eine Einigung erzielt?) bewertet. Das Wissenschaftszentrum Berlin für Sozialforschung (WZB) führt ein Forschungsprojekt zu Mediationsverfahren in der Umweltpolitik durch, dessen Hauptgegenstand eine Mediation zum Abfallwirtschaftskonzept des Kreises Neuss, Nordrhein-Westfalen, war. Im vorliegenden Papier werden einige Ergebnisse der sozialwissenschaftlichen Begleitforschung zusammengestellt, die es erlauben, den Erfolg dieses Verfahrens differenziert zu beurteilen. Im ersten Schritt wird der dem Mediationsverfahren zugrunde liegende Konflikt, das Verfahren und seine Ergebnisse dargestellt. Daran schließt sich eine Bewertung der Mediation an, wobei 18 zentrale verfahrens- und ergebnisorientierte Evaluationskriterien herangezogen werden. Die Analyse zeigt, daß die Evaluierung eines Mediationsverfahrens eine recht komplexe Angelegenheit ist und daß sich dies auch in den Bewertungen der Teilnehmer widerspiegelt.
Keywords: 300; Umweltpolitik; Verhandlungen; Abfallpolitik; Bewertung; Nordrhein-Westfalen